Peran Ekowisata dalam Konservasi Mangrove dan Daya Tarik Wisatawan di Pantai Mangrove Paluh Getah, Kabupaten Deli Serdang - Ruth Sahana Manalu; Maria Dwi Sianipar; Qamara Ananda Aulia; Meilinda Suriani Harefa (Tamasya : Jurnal Pariwisata Indonesia, 2025)
This study aims to examine the role of ecotourism in mangrove conservation and its appeal to tourists at Mangrove Beach Paluh Getah, Deli Serdang Regency. A qualitative approach was used, with data collected through direct observation and interviews with local communities and visitors. The findings indicate that ecotourism plays a significant role in rehabilitating mangrove ecosystems by engaging both residents and tourists in regular mangrove planting activities. Moreover, ecotourism positively impacts local livelihoods by promoting sustainable businesses such as tour guiding services and mangrove-based products. The natural beauty, biodiversity, and educational tourism programs serve as key attractions for visitors. Local communities actively manage the area through tourism awareness groups and cooperatives, enhancing both social and economic sustainability. However, challenges remain, including limited facilities and insufficient promotion. Therefore, sustainable development strategies involving collaboration between communities, the government, and the private sector are essential. Ecotourism at Paluh Getah Mangrove Beach holds great potential as a model for coastal area management that integrates conservation and community empowerment.